Cytokine Genetic Variants and Health-Related Quality of Life in Crohn's Disease: An Exploratory Study. Issue 5 (October 2019) - Knisely, Mitchell R.; Conley, Yvette P.; Szigethy, Eva
Background: Crohn's disease (CD) is an inflammatory condition that has deleterious effects on patients' health-related quality of life (HRQoL). Demographic, clinical, and psychosocial factors contribute to variability in HRQoL; however, the influence of genetic variations related to altered inflammatory responses in individuals with CD is unknown. This exploratory study compared HRQoL scores across genotypes of functional genetic polymorphisms in cytokine candidate genes among individuals with CD. Method: This study used data and blood samples collected in a parent study in 39 patients with CD aged 15−30 years. Participant reports of HRQoL were collected using the Shortened Inflammatory Bowel Disease Questionnaire (SIBDQ). Genetic data were collected for 18 functional polymorphisms in eight cytokine candidate genes. SIBDQ scores were compared among genotypes using one-way, between-subjects analysis of variance. Results: SIBDQ scores differed across genotypes as follows: for IL-1R2 rs4141134 scores differed for total SIBDQ ( p = .004) and systemic ( p = .011), emotion ( p = .038), and social domains ( p = .025); for IL-10 rs1878672, scores differed for total SIBDQ ( p = .031) and social domain ( p = .008); for NFKB2 rs1056890, scores differed for social domain ( p = .041); for TNF -α rs1800629, scores differed for total SIBDQ ( p = .001) and bowel ( p = .026), systemic ( p = .014), and social domains ( p = .045). Conclusions: Findings on differences in SIBDQ scores across functional genetic polymorphisms in cytokine genes suggest potential mechanisms that contribute to variability in HRQoL in adolescents and young adults with CD.